Respostas
respondido por:
1
6x + 2256 - 8x - 3864 = x - 510
6x - 8x - x = - 510 - 2256 + 3864
- 3x = - 1098 . (- 1)
x = 1098/3
x = 366
6x - 8x - x = - 510 - 2256 + 3864
- 3x = - 1098 . (- 1)
x = 1098/3
x = 366
Refazendo mais uma vez:
6x - 8x + x = - 510 - 2256 - 3864
- x = - 630 . (- 1)
x = 630
Agora sim, resposta definitiva :P
respondido por:
1
3(2x+752)-8(x-483)=-x-510
6x+2256-8x+3864=-x-510
6x-8x+x=-510-2256-3864
-1x=-6631 (-1)
x=6631
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
6x + 2256 - 8x + 3864 = x - 510
6x - 8x - x = - 510 - 2256 - 3864
- 3x = - 6630 . (-1)
x = 6630/3
x = 2210